Condições para a formação de supersólidos em condensados de Bose-Einstein excitônicos em semicondutores bidimensionais - Guimarães, Francisco Mateus Alves (2022)
The study of phase transitions and the search for new phases of matter continues, until the present day, has been a topic of great interest for the physics of condensed matter. Among these phases, we have the Bose-Einstein condensate, obtained when bosons under certain circumstances are cooled to extremely low temperatures. In this work, we focus on studying a system that has been investigated in several platforms, which are exciton condensates. In these systems, we study the behavior in the ground state of the BEC of excitons when the system presents a minimum of roton (elementary excitations). Thus, from a mean field approach, and through numerical solutions, we study the necessary conditions for the system to present a transition to the supersolid phase, that is, having both a long-range crystalline order and the property of flowing without friction. Introducing the potential presenting a roton minimum in the Gross-Pitaevskii equation and letting the wave function propagate in imaginary time, we obtain the profile of the system in the ground state.